Customer Continuance Usage of Digital Banking: A Systematic Review of Influencing Factors - Christy, Cathrine Abigael; Lisana, Lisana (Journal of Information System and Informatics, 2025)
Customer loyalty plays a crucial role in sustaining banking revenue and long-term growth. This study presents a systematic review that aims to provide insights for future studies about the trends of digital banking continuance usage intention. Using Population-Intervention-Comparison-Outcome-Time-Question (PICOTQ) Framework, this research focuses on journal articles published between 2020 and 2025, written in English, featuring a conceptualized research model, and published in peer-reviewed journals. Twenty-nine relevant articles were selected. The Preferred Reporting Items for Systematic Review (PRISMA) Framework guided the review process, revealing 56 variables used in related models. Among these, satisfaction, privacy and security, user experience, ease of use, and customer service and support were the most frequently significant factors influencing continuance usage. Most studies were conducted in Indonesia, India, and Korea, reflecting a variety of country income levels. The findings confirm that digital banking continuance usage intention remains a promising and prospective area for future investigation. Further exploration using diverse moderating variables and alternative analytical methods is encouraged to enrich understanding. Practically, this research offers valuable insights for digital banking stakeholders to strengthen customer loyalty by improving service quality, particularly by enhancing user satisfaction, strengthening data privacy and security, improving interface usability, and delivering responsive customer support.